Property Tax Restrictions on School Board Fiscal Taxing Authority in Pennsylvania - Timothy J. Shrom; William T. Hartman (Educational Considerations, 2014)
Historically, in Pennsylvania, the property tax has been the only significant local revenue source over which school boards have had authority, and their authority to raise property tax rates was unrestricted. This flexibility has proved helpful especially when the state has enacted unfunded mandates.
Keywords: Mandates; property tax; school district; Employment Cost Index; School Board; procedure; taxing authority; Pennsylvania school districts